Comparative analysis of proteomics and transcriptomics reveals novel mechanism underlying the antibacterial activity and immune-enhancing properties of horse milk - Chen, Xueshan; Gulbahar, Kawuli; Ding, Haiyan; Nie, Changhong; Gao, Xiaoli (Frontiers in Nutrition, 2025)
BackgroundHorse milk is a highly valuable organic food that is a promising alternative to cow milk, exhibiting plenty of healthy and immune benefits to human. However, identification of proteins associated human wellness and underlying molecular mechanism in horse milk remain unclear.MethodologyLabel-free mass spectrometry-based protein quantification technology was employed to investigate protein composition of animal milk, including cow, goat, camel and horse milk. Prokaryotic expression and disk diffusion assay were applied to acquire and evaluate in vitro antimicrobial activity of candidate proteins. RAW264.7 macrophage model cell line was used to validate effect of proteins on cytotoxicity, apoptosis and immune induction. ROS probe detected cell ROS change and RT-qPCR verified expression of immune response genes induced by proteins. Microscopy was used to observe the effects of protein on the morphological characteristics of bacteria, further transcriptome analysis was performed to investigate transcriptional changes of bacteria induced by candidate proteins.ResultsA total of 1,335 proteins was identified in cow, goat, camel and horse milk. GO enrichment analysis showed that the proteins related to protein degradation were highly expressed in horse milk compared to other three types of milk, contributing to easier assimilation and palatability. KEGG analysis showed that horse milk contained abundant antimicrobial associated proteins relevant to pathogenic bacterial resistance, leading to the decreased risk of pathogenic diseases. A higher accumulation of proteins associated with caffeine metabolism, amino acid biosynthesis, and glycolysis/gluconeogenesis in horse milk contributes to its distinctive flavor. Notably, highly expressed proteins in horse milk were closely linked to immune signaling pathways, functioning as immune modulators. Importantly, we identified four highly expressed antimicrobial associated proteins in horse milk including LPO, B2M, CD14 and PGL, among them, PGL functioned dually by in vitro antibacterial activity and immune activation. Further transcriptome analysis demonstrated that PGL exerted significant transcriptional changes to bacteria. Enrichment analysis showed PGL could inhibit growth of P. aeruginosa and E. coli by repressing the biosynthesis of secondary metabolites.ConclusionComparative proteomics revealed immune enhancement and nutrient composition of horse milk compared to cow, goat and camel milk. Identification of PGL showed antibacterial activity and potential medicinal value.